Pediatric and Adolescent Oncofertility : Best Practices and Emerging Technologies - Woodruff, Teresa K.; Gosiengfiao, Yasmin C. (Springer International Publishing : Imprint: Springer, 2017)
Reflecting the increasing interest in fertility management for pediatric and adolescent patients and fulfilling an urgent need to have a comprehensive guide to the management of these individuals, this is the first book of its kind to present a comprehensive discussion of pediatric and adolescent oncofertility. It carefully examines the impact of pediatric cancer and cancer therapy on fertility and presents both current and emerging fertility preservation techniques for both males and females, such as cryopreservation. Fertility concerns beyond cancer are also discussed, including disorders of sexual differentiation, gender dysphoria and thalassemia. Practical chapters on pediatric oncofertility in the clinic round out the book, covering setting up a practice, counseling and consent, disclosure and insurance considerations. Concluding chapters document fertility preservation techniques and outcomes internationally, with contributions from Portuguese, Brazilian and Japanese authors. Timely and wide-ranging, Pediatric and Adolescent Oncofertility is an ideal resource for reproductive medicine specialists, pediatric oncologists, and primary care physicians treating pediatric and adolescent cancer patients looking to protect fertility options.
Keywords: Medicine.; Endocrinology.; Oncology.; Pediatrics.; Reproductive medicine.; elektronické knihy; electronic books